1988
DOI: 10.1007/bf01067067
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in vocal activity rhythm: Fourier analysis of cyclicity in amount of talk

Abstract: Speakers in informal conversations tend to alternate regularly between lower and higher amounts of talking; the periods of these low/high activity cycles are on the order of 3, 6, and 15 minutes. Statistically significant periodicities occurred in 55% of the conversations studied. The periodograms that describe the partition of variance among periodic components show consistent individual differences in the cyclic patterning of vocal activity. Discriminant analysis used the amount of variance accounted for by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Warner & Mooney (1988) found t h a t individual speakers tended t o exhibit fairly consistent cycle lengths, even when paired with 3 different partners on 3 different occasions.…”
Section: Discussionmentioning
confidence: 95%
“…Warner & Mooney (1988) found t h a t individual speakers tended t o exhibit fairly consistent cycle lengths, even when paired with 3 different partners on 3 different occasions.…”
Section: Discussionmentioning
confidence: 95%
“…While individuals and different types of dyads generate relatively stable and characteristic temporal speech patterns, it has been shown that these patterns appear to be sensitive to a host of psychological, situational and perhaps even biological conditions (e.g., Warner & Mooney, 1988;Welkowitz et al, 1990). This is not surprising given that the phenomenon of CIT itself is interpreted to be an example of empathic behavior in that it reflect the familiarity with, and responsiveness of each conversationalist to the speech rhythms of the other (Welkowitz & Kuc, 1973).…”
Section: Measurements Of Reciprocal Influence In Conversationmentioning
confidence: 90%
“…Chappie's (1970) theory would predict this type of coupling between behavioral and physiological rhythms. Second, cycle lengths in amount of talk are fairly consistent within a speaker across different partners and occasions (Warner & Mooney, 1988). Chappie suggested that, because there are con-sistent individual differences in biological rhythms, one would expect similar individual differences in the cycle length of behavioral rhythms.…”
Section: Interpretation Ofautor2mentioning
confidence: 99%
“…In one, investigators who were primarily interested in partner influence used time series regression to obtain an R2INC that can be interpreted as an index of the strength of social influence (e.g., Levenson & Gottman, 1983). In the other, investigators who are primarily interested in cyclicity use frequency domain analyses to assess degree of cyclicity (e.g., Gottman & Ringland, 1981; Warner, 1979; Warner et al, 1983; Warner & Mooney, 1988). Some researchers have theorized that for certain types of dyads such as married couples, more predictable or structured interactions (and particularly interactions in which behaviors and physiological states are highly predictable between partners) are associated with negative affect or even clinical pathology (Gottman, 1979); this belief has been associated with a time series regression approach to interaction analysis.…”
Section: Relation Between Interaction Structure and Interaction Qualitymentioning
confidence: 99%